2017
DOI: 10.1089/gtmb.2016.0270
|View full text |Cite
|
Sign up to set email alerts
|

Micro RNA-146a But Not IRAK1 is Associated with Rheumatoid Arthritis in the Tunisian Population

Abstract: The IRAK1 rs3027898 was not associated with RA, whereas C allele of miR-146a rs2910164 was found to be protective. Functional studies are required to investigate the exact role of miR-146a rs2910164 during RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Recently, a study conducted on Tunisian population reveals a correlation of miR-146a and rheumatoid arthritis (RA), indicating that miR-146a might play a protective role in RA pathogenesis, which is mediated by plentiful pro-inflammatory cytokines through NF-kB pathways. [ 34 ] In addition, miR-146a expression in serum was illuminated to be negatively associated with the levels of TNF-α, IL-6, IL-8, and LTE-4 in AECOPD patients, and that miR-146a was negatively correlated with TNF-α, IL-6, IL-1β, IL-8, and LTE-4 levels in COPD patients in our study. The probable explanation of the correlation of miR-146a with those inflammatory cytokines may be that miR-146a is involved in the modulation of those cytokines expression.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Recently, a study conducted on Tunisian population reveals a correlation of miR-146a and rheumatoid arthritis (RA), indicating that miR-146a might play a protective role in RA pathogenesis, which is mediated by plentiful pro-inflammatory cytokines through NF-kB pathways. [ 34 ] In addition, miR-146a expression in serum was illuminated to be negatively associated with the levels of TNF-α, IL-6, IL-8, and LTE-4 in AECOPD patients, and that miR-146a was negatively correlated with TNF-α, IL-6, IL-1β, IL-8, and LTE-4 levels in COPD patients in our study. The probable explanation of the correlation of miR-146a with those inflammatory cytokines may be that miR-146a is involved in the modulation of those cytokines expression.…”
Section: Discussionmentioning
confidence: 49%
“…It might result from that the mechanisms of miR-146a/b mediating the levels of inflammatory cytokines reported by previous studies. [ 31 , 32 , 34 36 , 38 , 40 42 , 46 51 ]…”
Section: Discussionmentioning
confidence: 99%
“…Molecular epidemiological studies showed robust evidence that the presence of these genetic polymorphisms would be associated with a variety of diseases, such as inflammatory bowel [18], systemic lupus erythematosus (SLE) [19], some cancers [20] and RA [21,22]. Recently, studies assessing miR-146a rs2910164 or miR-499 rs3746444 polymorphism and risk of RA have been published [23–25], but the results are not always consistent. And other studies add to the evidence base of the associations of other miRNA polymorphism with arthritis risk but are not limited to RA – but not exclusively – the amount and impact of inflammation [24,26].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the systematic search and selection performed according to the inclusion and exclusion criteria are shown in Figure 1 . A total of 13 articles with 2660 cases and 4098 controls were finally included in the meta-analysis ( Chatzikyriakidou et al, 2010 ; Yang et al, 2011 , 2016 ; Jimenez-Morales et al, 2012 ; El-Shal et al, 2013 ; Hashemi et al, 2013 ; Zhang et al, 2013 ; Zhou X. et al, 2015 ; Bogunia-Kubik et al, 2016 ; Ciccacci et al, 2016 ; Toraih et al, 2016 ; Fattah et al, 2017 ; Hassine et al, 2017 ). The 13 articles comprised 16 studies, including 9 studies on miR-146a rs2910164 and 7 studies on miR-499 rs3746444.…”
Section: Resultsmentioning
confidence: 99%
“…A single nucleotide polymorphism consisting of the G/C nucleotide substitution in miR-146a rs2910164 could result in the replacement of a G:U pair by a C:U mismatch ( Hassine et al, 2017 ). However, the association between mir146a polymorphisms and RA remains controversial.…”
Section: Discussionmentioning
confidence: 99%